Instant Notes in Chemistry for Biologists - Fisher, J.; Arnold, J. R. P. (The instant notes series. Hames, B.D., editor of series, 1999)
First year undergraduates in the life sciences often have a limited background in chemistry, which therefore may prove to be a difficult subject to study at university level. This book covers the main concepts in chemistry, gives simple explanations for chemical terminology, and provides extensive biological examples to illustrate underlying principles and phenomena in the life sciences. Instant Notes in Chemistry for Biologist covers: The periodic table and isotopes Chemistry bonding & molecular shape Carbon, the basis of life on Earth Naming & classification of organic compounds Properties and reaction of organic compounds Isomerism & assignment of configuration Water & buffer solution Metals in biology Chemical synthesis of biological molecules Molecular interactions Chemical & enzyme kinetics Basic thermodynamics The electromagnetic spectrum and spectroscopic techniques. If you are studying biol